Predictive analytics for dummies - Bari, Anasse; Chaouchi, Mohamed; Jung, Tommy (John Wiley & Sons, 2016)
Business today relies on effectively using data to predict trends and sales. Predictive analytics is the tool that can make it happen, and this book eliminates the tricks and shows you how to use it. You'll learn to prepare and process your data, create goals, build a predictive model, get your organization's stakeholders on board and more.
Date of publication from resource description page. - Description based on online resource; title from cover (Safari, viewed November 4, 2016)
Keywords: Management -- Data processing; Management -- Mathematical models; Data mining; Data Mining; Gestion; Informatique; Gestion; Modèles mathématiques; Exploration de données (Informatique); Management; Data processing; Management; Mathematical models